The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1046/j.1365-2621.2002.00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Parboiling of rice. Part II: Effect of hot soaking time on the degree of starch gelatinization

Abstract: A differential scanning calorimetric study was done on raw and parboiled rice to determine the degree of gelatinization. Unparboiled rice absorbed the highest amount of endothermic heat, the enthalpy change gradually decreasing with increasing hot soaking time. The highest degree of gelatinization was achieved when the paddy was soaked for 120 min at 80 °C. With increasing degree of gelatinization, the yield point in a compression test also increased. During the parboiling process internal fissures were healed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
50
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 11 publications
10
50
0
1
Order By: Relevance
“…When soaking duration was 4 or 5 h, the water uptake capacity decreased slightly. The results were consistent with the previous study, which revealed that during the first soaking stage, the water could get into the rice by the capillary tube, so the water uptake proceeded rapidly (Miah et al 2002). Thakur and Gupta (2006) got the model equation of moisture absorption of different rice samples, and reported that the rate of moisture migration was dependent on the soaking temperature.…”
Section: Water Uptake Capacity Of Brown Ricesupporting
confidence: 90%
“…When soaking duration was 4 or 5 h, the water uptake capacity decreased slightly. The results were consistent with the previous study, which revealed that during the first soaking stage, the water could get into the rice by the capillary tube, so the water uptake proceeded rapidly (Miah et al 2002). Thakur and Gupta (2006) got the model equation of moisture absorption of different rice samples, and reported that the rate of moisture migration was dependent on the soaking temperature.…”
Section: Water Uptake Capacity Of Brown Ricesupporting
confidence: 90%
“…The observed values of gelatinisation temperatures are in the same range as those observed for native, extruded and parboiled rice flours (Kadan & Pepperman, 2002;Miah, Haque, Douglass, & Clarke, 2002). The enthalpy increases with increasing water activity for both the native and heat-treated samples.…”
Section: Impact Of Heat-treatment On Hydration and Gelatinization Behsupporting
confidence: 74%
“…Bello et al [10] reported that as steaming time was increased 45-75 min, the hardness of individual rice kernels was found to increase from 13.1 to 25.3 N. Islam et al [11] revealed that average hardness increased with increasing steaming time (60 min at 90 ∘ C and 10 min at 100 ∘ C). The effect of the parboiling process on the color value has been reported by many researchers [1,12,13]. The color value usually increases during parboiling while lightness decreases; the magnitude of the decrease in lightness increases with the severity of the parboiling process [14].…”
Section: Introductionmentioning
confidence: 90%
“…The color value ranged from 11.80 to 14.56, with the darkest color rice obtained at the highest steaming time (18.41 min), which can also be seen from Figures 6(b) and 6(c). The soaking temperature slightly affected the rice color, but steaming time greatly affected the rice color, as longer duration soaking and steaming led the rice bran pigments to penetrate into the endosperm [13,37]. The reaction of released sugar with an amino acid of grain during parboiling could lead to discoloration of rice [38].…”
Section: 6mentioning
confidence: 99%